Robust acute myeloid leukemia engraftment in humanized scaffolds using injectable biomaterials and intravenous xenotransplantation - Daniel Busa; Zdenka Herudkova; Jan Hyl; Jakub Vlazny; Filip Sokol; Kvetoslava Matulova; Adam Folta; Jakub Hynst; Lucy Vojtova; Leos Kren; Martin Repko; Zdenek Racil; et al. (Molecular Oncology)
Patient‐derived xenografts (PDXs) can be improved by implantation of a humanized niche. Nevertheless, the overall complexity of the current protocols, as well as the use of specific biomaterials and procedures, limits the wider adoption of this approach. Here, we identify the essential minimum steps required to create the humanized scaffolds and achieve successful acute myeloid leukemia (AML) engraftment. We compared seven biomaterials, which included both published and custom‐designed materials. The highest level of bone marrow niche was achieved with extracellular matrix gels and custom collagen fiber, both of which allowed for a simple non‐surgical implantation. The biomaterial selection did not influence the following AML infiltration. Regarding xenotransplantation, standard intravenous administration produced the most robust engraftment, even for two out of four otherwise non‐engrafting AML samples. In contrast, direct intra‐scaffold xenotransplantation did not offer any advantage. In summary, we demonstrate that the combination of an injectable biomaterial for scaffold creation plus an intravenous route for AML xenotransplantation provide the most convenient and robust approach to produce AML PDX using a humanized niche.